Rapid integrated parametric CAE modeling method of Linear Variable Differential Transformer based on a script template. (August 2015) - Kong, Xianguang; Chang, Shing I.; Yin, Lei; Zhong, Fulei
Highlights: Join CAD/CAE integration and CAE modeling method for the automatic parametric CAE modeling based on CAD model. Provide a software for the CAE modeling based on parameters. A more efficient and effective method based on a script template in LVDT simulations for the rapid integration between CAD and CAE and CAE modeling continuously. The parametric LVDT simulation can not only be rapidly established but also significantly improves the quality of LVDT design in industry. Abstract: Generally, Computing Aided Engineering (CAE) modeling and simulation of Linear Variable Differential Transformer (LVDT) has drawbacks such as the slow modeling speed and instability in simulation results. In this study, a rapid integrated parametric CAE modeling method is proposed for electromagnetic simulation based on a script template implemented in Maxwell electromagnetic simulation software with Visual Basic, so that the proposed method only requires the establishment of a simplified electromagnetic simulation model of a LVDT. The standard and parametric modeling process of LVDT is initially recorded as a script and then identifiers are added into the script to form a script template and transform Computing Aided Design (CAD) parameters to CAE modeling parameters according to parameter constraints of the model. Finally, parameter values are automatically assigned to identifiers in the script template in order to generate the script file through which the accurate CAE model can be created conveniently. The parametric LVDT simulation can not only be rapidly established but also significantly improves the quality of LVDT design in industry. In addition, the proposed method can improve CAD information availability in realizing seamless integration of CAD/CAE modeling in similar sensor product.